A multi-component rare earth synergistically doped high-entropy hafnium oxide ceramic, and a preparation method and application thereof

CN123003305APending Publication Date: 2026-10-30NANJING YOUTIAN METAL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611476257.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-22
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

现有少量的含铪高熵陶瓷研究多集中于具有中子吸收截面的铪酸盐,或通过造孔剂制备多孔陶瓷,这些材料无法充分发挥高熵晶格畸变、迟缓扩散效应对氧化铪高温相稳定、降低热导率的增益作用

Benefits of technology

[0010]本发明的技术效果和优点:1、本发明采用多组分稀土协同掺杂策略,成功构建了高熵稳定氧化铪陶瓷材料,多组分体系的大幅构型熵增产生了显著的“高熵效应”,利用该效应,使HfO2在高温条件下依旧保持单一稳定的相结构,解决了纯HfO2因高温相变伴随体积膨胀而导致开裂的问题;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003305A_ABST
    Figure CN123003305A_ABST
Patent Text Reader

Abstract

The application discloses a kind of multi-component rare earth synergic doped high-entropy hafnium oxide ceramic and its preparation method and application, the chemical general formula of the hafnium oxide ceramic is RE x Hf 1−x O 2−x / 2 Wherein, the RE includes the combination of multiple of Y, Yb, Er, Gd, Sm, Nd, La, and contains one or more than one large-radius light rare earth element, contains one or more than one small-radius heavy rare earth element.Multi-component rare earth synergic doping strategy is used, and high-entropy hafnium oxide ceramic material is successfully constructed, and the significant "high-entropy effect" is generated by the substantial configuration entropy increase of multi-component system, using the effect, HfO2 still maintains single stable phase structure under high temperature condition, solve the problem that pure HfO2 is cracked due to high temperature phase transition with volume expansion;Using the synergistic effect of high-entropy effect and sluggish diffusion effect, good high-temperature phase stability and good heat insulation performance are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of hafnium oxide ceramic technology, specifically relating to a high-entropy stable hafnium oxide ceramic with multi-component rare earth synergistic doping, its preparation method, and its application. Background Technology

[0002] With the rapid development of aerospace and gas turbine technologies, the operating temperatures of engine combustion chambers and turbine blades are constantly rising, posing increasingly severe challenges to the materials of hot-end components and their protective coatings—thermal barrier coatings. Traditional thermal barrier coatings use yttrium-stabilized zirconia (YSZ). However, when operating at temperatures above 1200°C for extended periods, this material is prone to a tetragonal-to-monoclinic phase transition, which directly damages the material structure. Furthermore, it rapidly densifies at high temperatures, significantly increasing internal stress and ultimately leading to coating peeling and failure.

[0003] Hafnium oxide (HfO2) has a melting point of approximately 2758℃, higher than zirconium oxide. Its crystal structure is similar to zirconium oxide, and its coefficient of thermal expansion is lower, making it a superior matrix material for preparing next-generation ultra-high temperature thermal protection materials. However, pure hafnium oxide undergoes multiple crystal transformations between monoclinic, tetragonal, and cubic phases during heating and cooling. The martensitic phase transformation from tetragonal to monoclinic (around 1600℃-1700℃ during cooling) is accompanied by a volume expansion of approximately 3%-5%. This drastic volume change caused by the phase transformation leads to enormous internal stress in the material during thermal cycling, resulting in cracking, spalling, and even pulverization of the ceramic body, severely limiting its engineering applications. Existing technologies typically employ the introduction of mono- or binary stabilizers to stabilize its high-temperature phase at room temperature, but the material still suffers from problems such as rapid element diffusion rates, insufficient resistance to sintering, and difficulty in further reducing thermal conductivity under ultra-high temperature conditions.

[0004] Currently, there are few reports on zirconia-based high-entropy ceramics. Studies have confirmed that the increased configurational entropy brought about by multi-rare earth co-doping can effectively stabilize the high-temperature crystalline phase and significantly reduce the thermal conductivity of the material. However, compared to zirconia, research on hafnium oxide-based high-entropy ceramics, which have better melting points and temperature resistance, is still in the preliminary exploratory stage. Existing limited research on hafnium-containing high-entropy ceramics mainly focuses on hafnium salts with neutron absorption cross sections or the preparation of porous ceramics using pore-forming agents. These materials cannot fully utilize the beneficial effects of high-entropy lattice distortion and slow diffusion on the high-temperature phase stability and reduced thermal conductivity of hafnium oxide. Therefore, how to utilize the synergistic mechanism of high-entropy effect and slow diffusion effect to develop hafnium oxide-based ceramics that simultaneously possess excellent high-temperature phase stability and ultra-low thermal conductivity is a key technical challenge that urgently needs to be overcome in the field of ultra-high temperature insulation materials. Summary of the Invention

[0005] The objective of the present invention is to provide a multi-component rare earth co-doped high-entropy stabilized hafnia ceramic, its preparation method and application, so as to solve the problems raised in the above background art.

[0006] To achieve the above objective, the present invention provides the following technical solution: A multi-component rare earth co-doped high-entropy stabilized hafnia ceramic, the chemical general formula of said hafnia ceramic is RE x Hf1 x O2 x / 2 , where RE is selected from a combination of multiple elements among Y (yttrium), Yb (ytterbium), Er (erbium), Gd (gadolinium), Sm (samarium), Nd (neodymium), and La (lanthanum), preferably 4 or 5 elements, and all rare earth elements are mixed in an equimolar ratio, that is, the proportion of each rare earth element in the total molar number of rare earth elements is 1 / n, where n is the total number of rare earth elements, and it must contain at least one large-radius light rare earth element (selected from La or / and Nd), and at least one small-radius heavy rare earth element (selected from Yb or / and Er); x is the total doping molar fraction of the rare earth elements, with a value range of 0.05<x≤0.4; preferably, the value range is 0.2≤x≤0.4.

[0007] The present invention further provides a preparation method of the multi-component rare earth co-doped high-entropy stabilized hafnia ceramic, comprising the following steps: (1) Weigh high-purity HfO2 powder and corresponding multiple rare earth oxide powders according to the stoichiometric ratio of the chemical general formula; (2) Put the mixed powder weighed in step (1) into a ball milling tank, use absolute ethanol or deionized water as the ball milling medium, and use zirconia balls or hafnia balls as the grinding balls, and perform ball milling and mixing to obtain a uniformly mixed slurry; (3) Dry the slurry obtained in step (2), grind and sieve it, a small amount of organic binder can be added, and granulate to obtain precursor powder; (4) Place the precursor powder of step (3) in a mold for uniaxial dry pressing and forming, and then perform cold isostatic pressing treatment to obtain a dense ceramic green body; (5) Place the ceramic green body of step (4) in a high-temperature sintering furnace for pressureless sintering, and cool it to room temperature with the furnace, so as to obtain the multi-component rare earth co-doped high-entropy stabilized hafnia ceramic material.

[0008] Preferably, the purity of the used high-purity HfO2 powder and rare earth oxide powder raw materials is both ≥99.9%; Preferably in any of the above solutions, the ball milling and mixing time is 12-24 hours, and the ball milling rotation speed is 200-300 rpm; In any of the above schemes, the preferred method is to use a drying temperature of 80-100℃, a drying time of 12-24 hours, and a sieve mesh of 100-200 mesh. Preferably, in any of the above embodiments, the organic binder is a polyvinyl butyral ethanol solution or a polyvinyl alcohol aqueous solution, and the amount added accounts for 0.5%-2% of the total mass of HfO2 powder and rare earth oxide powder; Preferred among the above options is that the unidirectional dry pressing pressure is 20-30 MPa and the holding time is 3-5 min, while the cold isostatic pressing pressure is 200-300 MPa and the holding time is 3-5 min. In any of the above schemes, the preferred sintering atmosphere is atmospheric, the sintering temperature is 1450℃-1650℃, the heating rate is 2-3℃ / min, and the sintering time is 4-10 hours.

[0009] The multi-component rare earth synergistic doped high-entropy stable hafnium oxide ceramic of the present invention, or the multi-component rare earth synergistic doped high-entropy stable hafnium oxide ceramic prepared by the preparation method of the present invention, can be processed into thermal barrier coating materials, heat insulation tiles for aero-engine combustion chambers, thermal protection components for hypersonic vehicles, or lining components for ultra-high temperature kilns.

[0010] The technical effects and advantages of this invention are as follows: 1. This invention adopts a multi-component rare earth synergistic doping strategy to successfully construct a high-entropy stable hafnium oxide ceramic material. The significant increase in configuration entropy of the multi-component system produces a significant "high-entropy effect". By utilizing this effect, HfO2 can still maintain a single stable phase structure under high temperature conditions, thus solving the problem of cracking caused by volume expansion accompanied by high-temperature phase transformation of pure HfO2. 2. This invention introduces multiple rare earth elements with different ionic radii and bond energies for co-doping, constructing a complex lattice environment and enhancing the mutual restraint between elements. This leads to a significant increase in the effective diffusion activation energy of cations in the lattice, thereby triggering a significant "slow diffusion effect." Based on this effect, this invention not only successfully overcomes the problems of element segregation and phase separation that are prone to occur in traditional single-doped systems, but also effectively suppresses abnormal grain growth of materials under high-temperature conditions. In addition, the co-doping of large-radius light rare earth elements and small-radius heavy rare earth elements not only maximizes the atomic size mismatch and enhances phonon scattering to reduce thermal conductivity, but also significantly increases the elastic strain energy of the lattice. 3. This invention utilizes the synergistic effect of high entropy effect and slow diffusion effect to achieve good high-temperature phase stability and good thermal insulation performance. Attached Figure Description

[0011] Figure 1 The XRD patterns are those of the samples prepared in Examples 1-3 and Comparative Examples 1-3 of this invention. Detailed Implementation

[0012] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0013] Example 1: (Y 0.2 Yb 0.2 La 0.2 Nd 0.2 Gd 0.2 ) 0.25 Hf 0.75 O 1.875 The preparation method of high-entropy hafnium oxide ceramics includes the following specific steps: Weigh out 157.87g of hafnium oxide, 5.65g of yttrium oxide, 9.85g of ytterbium oxide, 8.15g of lanthanum oxide, 8.41g of neodymium oxide, and 9.06g of gadolinium oxide according to the stoichiometric ratio. Place the weighed mixed powder into a ball mill jar, use deionized water as the ball milling medium and zirconia balls as the grinding balls, set the ball milling speed to 300 rpm, and ball mill for 24 hours to obtain a uniformly mixed slurry. The obtained slurry was dried at 100℃ for 24 hours, ground and passed through a 200-mesh sieve, and 2% polyvinyl alcohol aqueous solution was added to granulate the precursor powder. The precursor powder was placed in a mold and unidirectionally dry-pressed at a pressure of 30 MPa for 5 minutes; then it was subjected to cold isostatic pressing at a pressure of 300 MPa for 5 minutes to obtain a dense ceramic green body. The green blank was placed in a high-temperature sintering furnace and heated to 1650°C at a rate of 2°C / min under atmospheric conditions. It was then sintered without pressure for 4 hours and cooled to room temperature with the furnace to obtain (Y). 0.2 Yb 0.2 La 0.2 Nd 0.2 Gd 0.2 ) 0.25 Hf 0.75 O 1.875 High-entropy hafnium oxide ceramics.

[0014] Example 2: (La 0.2 Nd 0.2 Sm 0.2 Er 0.2 Yb 0.2 ) 0.4 Hf 0.6 O 1.8 The preparation method of high-entropy hafnium oxide ceramics includes the following specific steps: Weigh out 126.29g hafnium oxide, 13.03g lanthanum oxide, 13.46g neodymium oxide, 13.95g samarium oxide, 15.30g erbium oxide, and 15.76g ytterbium oxide according to the stoichiometric ratio. Place the weighed mixed powder into a ball mill jar, use deionized water as the ball milling medium and zirconia balls as the grinding balls, set the ball milling speed to 200 rpm, and ball mill for 20 hours to obtain a uniformly mixed slurry. The obtained slurry was dried at 80℃ for 20 hours, ground and passed through a 200-mesh sieve, and a polyvinyl alcohol aqueous solution accounting for 1.5% of the total mass of the powder was added and granulated to obtain the precursor powder. The precursor powder was placed in a mold and unidirectionally dry-pressed at a pressure of 25 MPa for 4 min; then it was subjected to cold isostatic pressing at a pressure of 250 MPa for 4 min to obtain a dense ceramic green body. The green blank was placed in a high-temperature sintering furnace and heated to 1600℃ at a rate of 3℃ / min under atmospheric conditions. It was then sintered without pressure for 6 hours and cooled to room temperature with the furnace to obtain (La). 0.2 Nd 0.2 Sm 0.2 Er 0.2 Yb 0.2 ) 0.4 Hf 0.6 O 1.8 High-entropy hafnium oxide ceramics.

[0015] Example 3: (Nd 0.25 Gd 0.25 Y 0.25 Er 0.25 ) 0.2 Hf 0.8 O 1.9 The preparation method of high-entropy hafnium oxide ceramics includes the following specific steps: Weigh out 168.39g of hafnium oxide, 8.41g of neodymium oxide, 9.06g of gadolinium oxide, 5.65g of yttrium oxide, and 9.56g of erbium oxide according to the stoichiometric ratio. Place the weighed mixed powder into a ball mill jar, use anhydrous ethanol as the ball milling medium and zirconia balls as the grinding balls, set the ball milling speed to 250 rpm, and ball mill for 12 hours to obtain a uniformly mixed slurry. The obtained slurry was dried at 80℃ for 12 hours, ground and passed through a 100-mesh sieve; a polyvinyl butyral ethanol solution accounting for 1% of the total mass of the powder was added, and the granulation was carried out to obtain the precursor powder. The precursor powder was placed in a mold and unidirectionally dry-pressed at a pressure of 20 MPa for 3 minutes; then it was subjected to cold isostatic pressing at a pressure of 200 MPa for 3 minutes to obtain a dense ceramic green body. The green blank was placed in a high-temperature sintering furnace and heated to 1550°C at a rate of 2°C / min under atmospheric conditions. It was then sintered without pressure for 8 hours and cooled to room temperature with the furnace to obtain (Nd... 0.25 Gd 0.25 Y 0.25 Er 0.25 ) 0.2 Hf 0.8 O 1.9 High-entropy hafnium oxide ceramics.

[0016] Comparative Example 1: (Y 0.25 Gd 0.25 Er 0.25 Yb 0.25 ) 0.25 Hf 0.75 O 1.875 The preparation method of heavy rare earth high-entropy hafnium oxide ceramics, the specific steps are as follows: Weigh out 157.87g hafnium oxide, 7.06g yttrium oxide, 11.33g gadolinium oxide, 11.95g erbium oxide, and 12.32g ytterbium oxide according to the stoichiometric ratio. The remaining components are as described in Example 1, to obtain (Y 0.25 Gd 0.25 Er 0.25 Yb 0.25 ) 0.25 Hf 0.75 O 1.875 Hafnium oxide ceramics with heavy rare earth elements and high entropy.

[0017] Comparative Example 2: Y 0.2 Hf 0.8 O 1.9 The preparation method of binary hafnium oxide ceramics, with specific steps as follows: Weigh 168.39g of hafnium oxide and 22.58g of yttrium oxide according to the stoichiometric ratio, and follow the procedure described in Example 3 to obtain Y. 0.2 Hf 0.8 O 1.9 Binary hafnium oxide ceramics.

[0018] Comparative Example 3: (Nd 0.25 Gd 0.25 Er 0.25 Yb 0.25 ) 0.1 Hf 0.9 O 1.95 The preparation method of high-entropy hafnium oxide ceramics includes the following specific steps: Weigh out 189.44g of hafnium oxide, 4.21g of neodymium oxide, 4.53g of gadolinium oxide, 4.78g of erbium oxide, and 4.93g of ytterbium oxide according to the stoichiometric ratio. Place the weighed mixed powder into a ball mill jar, use anhydrous ethanol as the ball milling medium and zirconia balls as the grinding balls, set the ball milling speed to 250 rpm, and ball mill for 12 hours to obtain a uniformly mixed slurry. The obtained slurry was dried at 80℃ for 12 hours, ground and passed through a 100-mesh sieve; a polyvinyl butyral solution accounting for 1% of the total mass of the powder was added, and the granulation was carried out to obtain the precursor powder. The precursor powder was placed in a mold and unidirectionally dry-pressed at a pressure of 20 MPa for 3 minutes; then it was subjected to cold isostatic pressing at a pressure of 200 MPa for 3 minutes to obtain a dense ceramic green body. The green blank was placed in a high-temperature sintering furnace and heated to 1550°C at a rate of 2°C / min under atmospheric conditions. It was then sintered without pressure for 8 hours and cooled to room temperature with the furnace to obtain (Nd... 0.25 Gd 0.25 Er 0.25 Yb 0.25 ) 0.1 Hf 0.9 O 1.95 High-entropy hafnium oxide ceramics.

[0019] The performance of hafnium oxide ceramics prepared in Examples 1-3 and Comparative Examples 1-3 was tested: 1. The thermal diffusivity of hafnium oxide ceramics at room temperature was measured using the laser flare method. The thermal conductivity was calculated based on the results shown in Table 1. κ = α·Cp·ρ; Where κ is thermal conductivity, α is thermal diffusivity, and Cp is the Neumann specific heat capacity at constant pressure. (Calculated using Kopp's rules), where ρ is the block density; Table 1: Thermal conductivity test results of each embodiment and comparative example

[0020] As shown in Table 1, the high-entropy multi-component design of this invention (Examples 1-3) has a significant technical effect on reducing the thermal conductivity of hafnium oxide ceramics. Comparative Example 1, which contains only heavy rare earth elements, has a rare earth doping amount of 0.25 and a thermal conductivity of 1.22 W·m. -1 ·K -1 The thermal conductivity is higher than that of Example 1, which contains light rare earth elements with the same doping amount, indicating that the co-doping of light and heavy rare earth elements can further enhance lattice distortion and achieve lower thermal conductivity. The room temperature thermal conductivity of the binary hafnium oxide ceramic (Comparative Example 2) is as high as 1.67 W·m. -1 ·K -1This invention constructs a high-entropy solid solution through co-doping with multiple rare earth elements. The lattice distortion effectively enhances phonon scattering, and the room-temperature thermal conductivity of all high-entropy samples decreases significantly. Among them, Example 2, with the highest rare earth doping concentration, has a room-temperature thermal conductivity of only 0.98 W·m. -1 ·K -1 Compared with binary hafnium oxide ceramic (Comparative Example 2), the thermal insulation performance is the best, with a reduction of 41.3%. When the doping concentration of the high-entropy system is too low (Comparative Example 3), the concentration of oxygen vacancies generated in the lattice is insufficient, and the point defect scattering cannot achieve the best effect. Its room temperature thermal conductivity is still higher than that of the present invention (Examples 1-3), but lower than that of binary hafnium oxide ceramic (Comparative Example 2).

[0021] 2. The phase structure of hafnium oxide ceramics was analyzed by XRD, such as... Figure 1 As shown, among them, Examples 1-3 (high entropy group): in the range of 20°-80°, the XRD patterns of these three samples showed sharp diffraction peaks only at approximately 30.2° (111), 35.0° (200), 50.4° (220), 59.8° (311), and 62.8° (222), which is in perfect agreement with the standard cubic fluorite phase; there were no impurity peaks near 28° and 31.5°, which proved that the multi-component high entropy design brought about a huge configurational entropy, which completely suppressed the martensitic phase transformation of hafnium oxide during the cooling process and achieved the stability of the fluorite phase at room temperature; after the binary hafnium oxide ceramic (Comparative Example 2) underwent extreme heat treatment at 1600°C for 100 hours, its spectrum showed two unusually strong diffraction peaks on both sides of the main peak (~28.2° and ~31.5°), which correspond to the (-111) and (111) crystal planes of the monoclinic phase. This indicates that traditional single-element doping cannot provide sufficient lattice distortion energy and configuration entropy, resulting in a large amount of room-temperature monoclinic phase residue. In Comparative Example 3, although it is a high-entropy system, the oxygen vacancy concentration and absolute value of configuration entropy are insufficient to completely offset the free energy of the monoclinic phase transition, resulting in a small number of monoclinic phase characteristic peaks in the spectrum. This defines the concentration threshold for a fully stable cubic phase in high-entropy hafnium oxide. In Comparative Example 1 (heavy rare earth high-entropy ceramic), its phase stabilization ability is slightly inferior, resulting in the precipitation of a small amount of monoclinic phase at the grain boundaries.

[0022] The results of the analysis are shown in Table 2. Table 2: Comparison of phase structures before and after annealing in each embodiment and the comparative example

[0023] As shown in Table 2, Comparative Example 1 (heavy rare earth high-entropy ceramic) exhibited insufficient lattice distortion due to similar ionic radii, resulting in a small amount of monoclinic phase degradation after annealing at 1600℃. Binary hafnium oxide ceramic (Comparative Example 2) underwent severe phase separation and degradation after 100 hours of extreme heat treatment at 1600℃, with a large amount of the original fluorite phase degenerating into the monoclinic phase, completely losing phase stability. When the doping concentration of the high-entropy system was too low (Comparative Example 3), a small amount of monoclinic phase precipitation occurred after annealing due to insufficient oxygen vacancy concentration. However, compared to binary hafnium oxide ceramic (Comparative Example 2), its phase stability was significantly improved. In Examples 1 to 3 of the present invention (using a mixed high-entropy system of light and heavy rare earths with doping amounts of 20% to 40%), after undergoing the same stringent annealing conditions, 100% of the fluorite phase was maintained before and after annealing, without any phase transformation or phase separation. This further proves that the multi-component rare earth synergistic doping high-entropy stable hafnium oxide ceramics prepared by the present invention (especially the large-size mismatch combination of light and heavy rare earths) constructs a complex lattice environment, thereby generating a significant "slow diffusion effect", which greatly raises the atomic transition barrier and effectively blocks the long-range migration of cations at extreme high temperatures, thus achieving good high-temperature phase stability.

[0024] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A high-entropy stable hafnium oxide ceramic with multi-component rare earth synergistic doping, characterized in that, The general chemical formula of the hafnium oxide ceramic is RE x Hf 1−x O 2−x / 2 ,in, The RE includes a combination of multiple elements such as Y, Yb, Er, Gd, Sm, Nd, and La, and contains one or more large-radius light rare earth elements and one or more small-radius heavy rare earth elements. The value of x is in the range of 0.

05. <x≤0.4。 2. The high-entropy stable hafnium oxide ceramic with multi-component rare earth synergistic doping according to claim 1, characterized in that, The RE includes a combination of four of the following: Y, Yb, Er, Gd, Sm, Nd, and La.

3. The high-entropy stable hafnium oxide ceramic with multi-component rare earth synergistic doping according to claim 1, characterized in that, The RE includes a combination of five of the following: Y, Yb, Er, Gd, Sm, Nd, and La.

4. The high-entropy stable hafnium oxide ceramic with multi-component rare earth synergistic doping according to claim 1, characterized in that, The large-radius light rare earth elements include La and Nd, and the small-radius heavy rare earth elements include Yb and Er.

5. The high-entropy stable hafnium oxide ceramic with multi-component rare earth synergistic doping according to claim 1, characterized in that, The value of x is in the range of 0.20 ≤ x ≤ 0.

40.

6. A method for preparing high-entropy stable hafnium oxide ceramics with multi-component rare earth synergistic doping, characterized in that, Includes the following steps: S1: Weigh HfO2 powder and rare earth oxide powder and put them into a ball mill jar. Use anhydrous ethanol or deionized water as the ball milling medium and zirconium oxide balls or hafnium oxide balls as grinding balls to ball mill and mix them to obtain a uniformly mixed slurry. S2: Dry the slurry obtained in the above steps, grind and sieve it, add an organic binder, the organic binder accounts for 0.5%-2% of the total mass of HfO2 powder and rare earth oxide powder, and granulate to obtain precursor powder; S3: The precursor powder obtained in the above steps is placed in a mold for unidirectional dry pressing and then subjected to cold isostatic pressing to obtain a dense ceramic blank. S4: Place the ceramic green body obtained in the above steps into a high-temperature sintering furnace for pressureless sintering. The sintering atmosphere is atmospheric. The sintering temperature is 1450℃-1650℃, the heating rate is 2-3℃ / min, and the sintering time is 4-10 hours. Finally, cool it to room temperature with the furnace to obtain a high-entropy stable hafnium oxide ceramic material with multi-component rare earth synergistic doping.

7. The method for preparing a high-entropy stable hafnium oxide ceramic with multi-component rare earth synergistic doping according to claim 6, characterized in that, In step S1, the ball milling mixing time is 12-24 hours, and the ball milling speed is 200-300 rpm.

8. The method for preparing a high-entropy stable hafnium oxide ceramic with multi-component rare earth synergistic doping according to claim 6, characterized in that, In step S2, the drying temperature is 80-100℃, the drying time is 12-24 hours, and the sieve used is 100-200 mesh.

9. The method for preparing a high-entropy stable hafnium oxide ceramic with multi-component rare earth synergistic doping according to claim 6, characterized in that, The pressure for unidirectional dry pressing is 20-30 MPa, and the holding time is 3-5 min. The pressure for cold isostatic pressing is 200-300 MPa, and the holding time is 3-5 min.

10. The application of hafnium oxide ceramic according to any one of claims 1-5 or hafnium oxide ceramic prepared by any one of claims 6-9 in the preparation of thermal barrier coating materials, heat insulation tiles for aero-engine combustion chambers, thermal protection components for hypersonic aircraft, or lining components for ultra-high temperature kilns.